ADDITIONAL PROGRAMS IN LANGUAGE DEVELOPMENT AND READING RECOGNITION SKILLS IN EARLY CHILDHOOD - Ubaidillah Ubaidillah; Moh. Syamsi (Atthiflah: Journal of Early Childhood Islamic Education, 2023)
Reading in everyday life is very important, because by reading we can know the information written. In frequent reading, people can master a lot of vocabulary, and can learn different types or models of sentences. Therefore, to improve reading it must be taught early. This study was conducted to determine the implementation of the additional class program for group B children at Al Muchlisin Islamic Plus Kindergarten. The form of research is descriptive qualitative which concludes that in improving the ability to recognize reading in children through additional program activities, there are several factors that affect the effectiveness of the additional class program in improving the ability to recognize reading in group B children at Al Muchlisin Islamic Plus Kindergarten, including: the spirit of motivation from students, the spirit of interest in learning to read students, and full support from parents. The effectiveness of the additional class program in improving the ability to recognize reading in group B children at TK Islam Plus Al Muchlisin showed good development results, this is evident from all students who were able to take part in these various activities were BSH (Developing According to Expectations) from 20 students.